2017
DOI: 10.1590/1984-70332017v17n2n24
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming crossing barriers between jatropha (Jatropha curcas L.) and castor bean (Ricinus communisL.)

Abstract: Abstract:A limitation in improvement of jatropha (Jatropha curcas)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Jatropha succeeds in crossing with other species in its genus, such as J. integerrima Jacq. (Laosatit et al 2017;Fukuhara et al 2016). Inter-speci c hybridization can help widen the genetic base of Jatropha, thereby making it more widely distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Jatropha succeeds in crossing with other species in its genus, such as J. integerrima Jacq. (Laosatit et al 2017;Fukuhara et al 2016). Inter-speci c hybridization can help widen the genetic base of Jatropha, thereby making it more widely distributed.…”
Section: Introductionmentioning
confidence: 99%
“…curcas L. However, pre- and post-fertilization barriers affect the hybridization process [10]. Laosatit et al [10] reported on embryo abortion, a post-fertilization barrier, which was overcome by ovule culture. Sterility of F 1 hybrids is also very common in intergeneric hybridization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Jatropha curcas is a monoecious species with unisexual flowers (Montes and Melchinger, 2016); xenogamic (Divakara et al, 2010;de Argollo Marques et al, 2013); self-compatible (Chang-Wei et al, 2007;Brasileiro et al, 2012), and diploid (2n = 2x = 22), as well as most congeners species (Carvalho et al, 2008;Sasikala and Paramathma, 2010;Marinho et al, 2018). These traits allow crosses between Jatropha species, although with limited success due to either pre-or post-zygotic barriers (Moreira et al, 2013), which can be overcome using in vitro embryo rescue technique (Laosatit et al, 2017). However, several successful crosses have been reported, for instance, between J. curcas and J. integerrima, aiming at shorter plants, higher seed oil yield, resistance to diseases, woody biomass, etc (Sujatha and Prabakaran, 2003;Parthiban et al, 2009;One et al, 2014).…”
Section: Introductionmentioning
confidence: 99%